2016
DOI: 10.1159/000447794
|View full text |Cite
|
Sign up to set email alerts
|

Plasma MicroRNA-126-5p is Associated with the Complexity and Severity of Coronary Artery Disease in Patients with Stable Angina Pectoris

Abstract: Background: Coronary artery disease (CAD) is a major problem worldwide. As an endothelium-enriched microRNA (miRNA), miR-126 has been reported to serve as a potential biomarker of acute myocardial infarction. However, the relationship between miR-126 and the severity of CAD remains unknown. This study was designed to test whether circulating miR-126 levels are associated with the severity of CAD. Methods: The present study enrolled 40 patients who had risk factors for CAD without angiographically significant C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 39 publications
3
34
0
Order By: Relevance
“…Importantly, miR-126 has been shown to correlate with PR in patients with ACS and is likely a strong marker of platelet function 15 . MiR-126-5p promotes endothelial proliferation and www.nature.com/scientificreports www.nature.com/scientificreports/ endothelial cell stability and has been implicated in protective properties including limiting atherosclerosis by suppressing Notch1 inhibitor delta-like 1 homolog and reducing thrombogenicity in diabetes mellitus by targeting tissue factor [28][29][30] . It is therefore credible that lower PR (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, miR-126 has been shown to correlate with PR in patients with ACS and is likely a strong marker of platelet function 15 . MiR-126-5p promotes endothelial proliferation and www.nature.com/scientificreports www.nature.com/scientificreports/ endothelial cell stability and has been implicated in protective properties including limiting atherosclerosis by suppressing Notch1 inhibitor delta-like 1 homolog and reducing thrombogenicity in diabetes mellitus by targeting tissue factor [28][29][30] . It is therefore credible that lower PR (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-126 has played significant roles in different physiological and pathological processes, including inflammation, blood vessel growth, and cancer through various pathways [24]. Circulating miR-126-5p has been reported as an underlying biomarker for the complexity and severity of Coronary Artery Disease (CAD) in patients with stable angina pectoris [26]. Additionally, the effect of miR-126 on vascular inflammation is regulated by adhesion molecule-1 [27].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also reported that some miRNAs have differential expression patterns depending on the disease pathology. miR-126 levels are elevated in patients with atrial fibrillation and heart failure [162], while conversely low levels are reported in patients with angina or AMI [151,163,164], highlighting a diverse role for miR-126 in the cardiovascular system. Circulating levels of several 14q32 miRNAs (miR-134, miR-328, miR-370, miR-480 and miR-487a/b) also possess diagnostic value for CAD, AMI and cardiac death, respectively [161,[165][166][167].…”
Section: Circulating Mirnas As Potential Clinical Biomarkers For Athementioning
confidence: 99%